Pengiriman data hasil pengukuran parameter lingkungan menggunakan jaringan seluler dengan Raspberry Pi sebagai node - Husen Nasrullah Armin; Isnain Gunadi; Catur Edi Widodo (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
In this research has built a data delivery system of environmental parameters from Raspberry Pi into a webserver database for monitoring temperature, humidity, and light intensity in realtime, which used two Raspberry Pi as the two sensor nodes. Data from measurement of temperature, humidity, and light intensity of the sensor node is transmitted into the webserver via the mobile network, then the data is stored in a MySQL database, then the data is displayed in the form of websites. Applications to display the information of temperature, humidity and light intensity are made in the form of web programming with PHP and HTML discussed. With the appearance of the web is expected to facilitate the users to access through related information anywhere and anytime with the terms connected to the network internet. from this study, obtained results Raspberry Pi is able to transmit the observed data well into the webserver with a minimum data transmission delay of 1 second and 12 second maximum delay for a sensor node-1 and minimum delivery delays 1 second and 13 second maximum delay for sensor node-2.Keywords : Raspberry Pi , webserver, PHP, MySQL